Epidemiological characteristics of respiratory pathogens infections among children after the removal of non-pharmaceutical interventions in central China - Shun Liu; Yao Lei; Xiuxiu Chen; Zihan Wen; Bing Mei (Virology Journal)
Abstract Background During the COVID-19 pandemic between 2020 and 2022 in China, various non-pharmaceutical interventions (NPIs) were implemented to reduce the spread of SARS-CoV-2 and other respiratory pathogens. From 2023, China downgraded the management of COVID-19, and compliance with NPIs was no longer mandatory. This study aimed to reveal the epidemiological characteristics of respiratory pathogens in 2023 after the removal of NPIs in central China. Methods Respiratory specimens of children with acute respiratory infections (ARIs) were obtained to detect seven common respiratory pathogens, including influenza A (FluA), influenza B (FluB), adenovirus (ADV), human rhinovirus (HRV), human respiratory syncytial virus (HRSV), human metapneumovirus (HMPV), Mycoplasma pneumoniae (MP). From January 2022 to December 2023, a total of 5423 specimens were collected, including 1122 children in 2022 and 4301 children in 2023. Results One or more pathogens were detected in 62.50% specimens in 2023, significantly higher than that in 2022 (44.12%). HRV (13.81%) was the most common pathogen in 2022, whereas MP (24.67%) was predominant in 2023. There was no significant difference in the overall prevalence of HRV, HRSV and HMPV between 2022 and 2023. HRSV was the most common pathogen in the < 1 years children both in 2022 and 2023. However in the ≥ 7 years group, FluB was the predominant pathogen in 2022 whereas MP ranked first in 2023. Co-detection were significantly more frequent in 2023 compared to 2022. Conclusions The removal of NPIs significantly increased the infection rates of the respiratory pathogens among children. Some NPIs, such as wearing mask and hand hygiene are necessary to decrease the prevalence of certain pathogens.